Engineering cannabidiol synergistic carbon monoxide nanocomplexes to enhance cancer therapy via excessive autophagy - Chang Xiao; Yue Sun; Jialong Fan; William Nguyen; Simin Chen; Ying Long; Wei Chen; Aiguo Zhu; Bin Liu (Elsevier, 2023)
Although carbon monoxide (CO)-based treatments have demonstrated the high cancer efficacy by promoting mitochondrial damage and core-region penetrating ability, the efficiency was often compromised by protective autophagy (mitophagy). Herein, cannabidiol (CBD) is integrated into biomimetic carbon monoxide nanocomplexes (HMPOC@M) to address this issue by inducing excessive autophagy. The biomimetic membrane not only prevents premature drugs leakage, but also prolongs blood circulation for tumor enrichment. After entering the acidic tumor microenvironment, carbon monoxide (CO) donors are stimulated by hydrogen oxide (H2O2) to disintegrate into CO and Mn2+. The comprehensive effect of CO/Mn2+ and CBD can induce ROS-mediated cell apoptosis. In addition, HMPOC@M-mediated excessive autophagy can promote cancer cell death by increasing autophagic flux via class III PI3K/BECN1 complex activation and blocking autolysosome degradation via LAMP1 downregulation. Furthermore, in vivo experiments showed that HMPOC@M+ laser strongly inhibited tumor growth and attenuated liver and lung metastases by downregulating VEGF and MMP9 proteins. This strategy may highlight the pro-death role of excessive autophagy in TNBC treatment, providing a novel yet versatile avenue to enhance the efficacy of CO treatments. Importantly, this work also indicated the applicability of CBD for triple-negative breast cancer (TNBC) therapy through excessive autophagy.